Silicon carbide powder mixed micro electro discharge milling of titanium alloy - Ali, Mohammad Yeakub; N.A.R.A., Atiqah; M.A., Erniyati (Universiti Malaya, 2011)
This paper presents the influence of silicon carbide (SiC) powder concentration in dielectric fluid and electrical discharge energy in micro electro discharge machining (μEDM) of titanium alloy (Ti-6Al-4V) with tungsten carbide (WC) electrode. SiC powder concentration and electrical discharge energy were two input variables. Three responses namely surface roughness (Ra), material removal rate (MRR), and electrode wear rate (EWR) were investigated. Sixteen experiments were conducted by using two factor and four level (42) full factorial design of experiment. Data were analyzed by Design Expert® software. A multi criteria optimization on low Ra, high MRR and low EWR has been achieved which showed 2.68 µm Ra., 6.908 µg/min MRR and 1.518 µg/min EWRfor the input parameters of 15.42 g/l SiC powder concentration and 54.28 µJ discharge energy. The analysis of variance revealed that powder concentrations are the most influential parameter on Ra. The optimization of MRR and EWR are mostly influenced by electrical discharge energy